2023
DOI: 10.1126/sciadv.add9973
|View full text |Cite
|
Sign up to set email alerts
|

The South American monsoon approaches a critical transition in response to deforestation

Nils Bochow,
Niklas Boers

Abstract: The Amazon rainforest is threatened by land-use change and increasing drought and fire frequency. Studies suggest an abrupt dieback of large parts of the rainforest after partial forest loss, but the critical threshold, underlying mechanisms, and possible impacts of forest degradation on the monsoon circulation remain uncertain. Here, we use a nonlinear dynamical model of the moisture transport and recycling across the Amazon to identify several precursor signals for a critical transition in the coupled atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Hence, the equilibrium assumption of CSD, whereby a slow change in the external forcing only changes the equilibrium state, but does not keep the system in disequilibrium for long, may be violated. Nevertheless, studies have found that the Amazon rainforest may approach a tipping point due to deforestation [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the equilibrium assumption of CSD, whereby a slow change in the external forcing only changes the equilibrium state, but does not keep the system in disequilibrium for long, may be violated. Nevertheless, studies have found that the Amazon rainforest may approach a tipping point due to deforestation [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…These events are taking place at a time when the Amazon rainforest is moving towards a "tipping point", especially those regions undergoing intense forest degradation and deforestation, characterized by a warming trend 3,4 , a lengthening of the dry season 5,7 and a decline of the Amazon carbon sink 1,8 . Both, climate change and Amazon deforestation, are considered as main drivers of this biophysical transition in Amazonia [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Conclusion and Final Commentsmentioning
confidence: 99%
“…High deforestation rates regionally affect the hydrological cycle in the Amazon basin [41][42][43] . Deforestation reduces the latent heat (evapotranspiration) and increases the sensible heat, contributing to the heating of the lower atmosphere and reducing the amount of water vapor in the atmosphere [33][34][35][36] . In addition, the hot and www.nature.com/scientificreports/ dry conditions favor the occurrence of anthropogenic large-scale fires 7,44 .…”
Section: Conclusion and Final Commentsmentioning
confidence: 99%
“…Evidence is all around us that we are nearing or have already crossed CTPs associated with critical parts of the Earth system-we see catastrophic fires in rainforests, spreading deserts, degrading ecosystems, and shrinking sea ice (e.g., Walsh, 2016;Bochow and Boers, 2023;Kim et al, 2023).…”
Section: Introductionmentioning
confidence: 99%